Un diálogo recuperado de Juan Ginés de Sepúlveda: De pugna legum dirimenda (I) - Solana Pujalte, Julián; García Pinilla, Ignacio J. (1997)
En este artículo se recoge toda la documentación hallada sobre un diálogo, De pugna legum dirimenda, sin duda escrito por el humanista Juan Ginés de Sepúlveda y perdido hasta hoy. Después se comunica el hallazgo de una copia de esta obra (cuya edición queda paramás adelante) en el ms. 5785 de la Biblioteca Nacional de Madrid.
This article studies alí the available documents about De pugna legum dirimenda, an humanistic dialog undoubtedly written by Juan Ginés de Sepúlveda and which remained np to now unfindable. The authors assert that they have find a copy of that work in the Biblioteca Nacional in Madrid, ms. 5785. They announce that they are preparing a forthcoining edition of it.
Keywords: Sepúlveda, Juan Ginés de; Diálogos